LESS is happiness: Sufficiency and good life in urban design (EAAE Annual Conference Proceedings, 2024)
Thus far, the strategies of efficiency and consistency alone were hardly capable of reducing the consumption of resources in the overall ecological balance of the construction industry. Therefore, sufficiency – a rather undervalued sustainability pathway – comes into play, especially in the wider field of urban design and under consideration of societal aspects. However, in urban design education, the concept of sufficiency has only received fleeting recognition and application. This panel looked for contributions on teaching formats that deal with notions of “lifestyles of restraint” or more comprehensive approaches of transforming urban environments in relation to sufficiency. This led to the focal question and subsequent topics to be explored:How can sufficiency play a role in the teaching of urban design as a parameter conditioning both the production of space and the integration of people?• How can education incorporate strategies for incentivizing certain behaviours oriented on sufficiency in urban design?• How can sufficiency be conceived as a benefit, instead of a sacrifice?• To which degree can user-based urban design or the inclusion of DIY-methods become vectors for sufficiency?• How can we define design criteria for “sufficiency”, “happiness” and “good life” in urban design?• How can the design of scenarios communicate appealing “lifestyles of restraint” for users of architecture?• Which methods of utopian prototyping are capable of envisioning lifestyles of sufficiency and happiness attractive to future users?• To what extent can architectural education be charged with futures literacy?